2000
DOI: 10.1136/bmj.320.7234.537
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic reviews and meta-analyses on treatment of asthma: critical evaluation

Abstract: Objective To evaluate the clinical, methodological, and reporting aspects of systematic reviews and meta-analyses on the treatment of asthma and to compare those published by the Cochrane Collaboration with those published in paper based journals. Design Analysis of studies identified from Medline, CINAHL, HealthSTAR, EMBASE, Cochrane Library, personal collections, and reference lists. Studies Articles describing a systematic review or a meta-analysis of the treatment of asthma that were published as a full re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 20 publications
4
129
0
2
Order By: Relevance
“…95 A Cochrane review by Haynes and colleagues 88,89 examined a diverse range of interventions designed to promote adherence with prescribed medications across a number of medical and psychiatric conditions. Five relevant interventions in asthma were included amongst the total of 33 studies reviewed, two of which showed clear effects on adherence and treatment outcomes in favour of the intervention.…”
Section: Psycho-educational Interventions In Mixed Diseasesmentioning
confidence: 99%
“…95 A Cochrane review by Haynes and colleagues 88,89 examined a diverse range of interventions designed to promote adherence with prescribed medications across a number of medical and psychiatric conditions. Five relevant interventions in asthma were included amongst the total of 33 studies reviewed, two of which showed clear effects on adherence and treatment outcomes in favour of the intervention.…”
Section: Psycho-educational Interventions In Mixed Diseasesmentioning
confidence: 99%
“…Previous studies attempted to review systematic reviews and meta-analyses in the fields of asthma (Jadad et al, 2000), back and neck pain (Assendelft et al, 1995;Furlan et al, 2001;Hoving et al, 2001), analgesia and anaesthesia (Jadad and McQuay, 1996;Choi et al, 2001), emergency medicine (Kelly et al, 2001) and surgery (Dixon et al, 2005). With no exception, those studies discussed the (predominantly low) quality of systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, systematic reviews are considered a scientific exercise in itself. However, still a considerable amount of so-called systematic reviews, especially those sponsored by the industry or non-Cochrane reviews, appear to have methodological flaws (Jadad et al, 2000). Moreover, studies on the same topic that were found to be of good quality may produce contradictory evidence (Jadad and McQuay, 1996;Furlan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jadad and colleagues (Jadad, Moher, Browman, Booker, Sigouin, Fuentes, et al, 2000) analyzed 50 systematic reviews and meta-analyses of asthma treatment and found that most reviews published in peer-reviewed journals had serious methodological flaws that limited their usefulness; Cochrane reviews were more rigorous and better reported than those published in peer-reviewed journals. All industry-funded reviews were judged to have serious flaws.…”
Section: Current Practicementioning
confidence: 99%